P.101 Conservative management of meningiomas with a moderate to high peritumoral brain edema index: a single-institution report. (June 2019) - Yan, H; Karmur, B; Jeong, D; Bernstein, M
Abstract : Background: Meningiomas are the most commonly occurring benign intracranial tumors. When presenting with peritumoral brain edema (PTBE), surgical treatment can lead to patient morbidity. This retrospective case series aims to describe the conservative medical management of moderate to large meningiomas with large PTBE. Methods: Patients with suspected meningiomas greater than 2.0cm and edema index greater than 2.0 were identified by screening 3345 MRI scans between 2012-2017. Imaging analysis included MR imaging features of suspected meningiomas and clinical data was gathered from the electronic patient record (patient age, sex, patient symptoms, follow-up duration, and follow-up symptoms). Results: We report on 31 patients who received conservative medical management. Presenting complaints included headache, seizure, weakness; many presented asymptomatically. The average follow-up time was 3.96 years. At the final follow-up appointment, 19 (61%) patients were asymptomatic. Among symptomatic patients, seizures were the most common complaint. There was no mortality reported in our cohort and the average tumor progression was 7.04cm3/year. Conclusions: In this retrospective report of meningioma patients with high edema index, we found that most patients remained asymptomatic or had stable symptoms after at least 1-yr follow up after medical treatment. This study provides insight around the surgical decision-making for meningiomas with large spread of edema.